Factors of Affecting Early Marriage on Adolescent Women in Sei Buluh Village, Sei Bamban District - Asrul; Miskah Afriani; Titiadi Simamora (International Journal of Cultural and Social Science, 2021)
In terms of socio-economic, mental/psychological, and physical health, early marriage in adolescents has a negative impact on the teen's reproductive health. As a result of early marriage, women between the ages of 15 and 19 are twice as likely to die in childbirth. This is a correlational and cross-sectional approach to research. Teenagers aged 15 to 20 years who had married young were included in this study. The logistic regression test was used for the analysis. According to the study's findings, the perception of culture is the most influential factor, while promiscuity has no effect. If you find your children dating in inappropriate places, you can suggest marriage as a way of improving your economic and cultural life. Children's mental and physical health is at risk when parents marry young, according to this study.